2023
DOI: 10.1039/d3tc00016h
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous carbon material of daily carbon ink: emerging applications in pressure, strain, and humidity sensors

Abstract: Carbon based materials have been widely used in various sensors. In addition to widely reported graphene, carbon nanotubes and their composites, low-cost amorphous carbon materials are also sought after. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 121 publications
0
32
0
Order By: Relevance
“…The relative standard deviation of the response in the reproducibility test was calculated to be 5.1%. Further, the stability to humidity change is important for the sensor working at room temperature; 64–66 the MoSe 2 –SeVO2 sensor exhibited good stability in the humidity range from 30% to 70% changes (Fig. S12†).…”
Section: Resultsmentioning
confidence: 99%
“…The relative standard deviation of the response in the reproducibility test was calculated to be 5.1%. Further, the stability to humidity change is important for the sensor working at room temperature; 64–66 the MoSe 2 –SeVO2 sensor exhibited good stability in the humidity range from 30% to 70% changes (Fig. S12†).…”
Section: Resultsmentioning
confidence: 99%
“…Strain sensors are used in various applications such as human–machine interfaces, robotic smart skins, health care monitoring, and bio-integrated devices. 1,2 Paper-based strain sensors can be classified into three types based on their working modes: bending, 3,4 pressure, 5,6 and tensile 7,8 sensors. However, only bending and pressure sensors are typically considered for flexible paper-based strain sensors due to the limited stretchable properties of paper, 4,9,10 which limit the potential of sensing to only small strain ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ionogels have fostered an increasing interest in flexible sensors, such as pressure sensors, , gas sensors, , humidity sensors, temperature sensors, , and strain sensors in recent years. Flexible strain sensors in particular, which monitor the mechanical deformation of substrates, have attracted considerable attention in healthcare and human motion detection applications; the main type of strain sensors is the resistance type . Earlier this year, Zhao et al reported highly conductive, polyurethane-based ionogels for monitoring physiological signals.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible strain sensors in particular, which monitor the mechanical deformation of substrates, have attracted considerable attention in healthcare and human motion detection applications; 16−19 the main type of strain sensors is the resistance type. 20 Earlier this year, Zhao et al 21 reported highly conductive, polyurethane-based ionogels for monitoring physiological signals. They achieved high conductivities by introducing carboxyl groups into the hard segments of the polyurethane, which created ion exchange sites.…”
Section: Introductionmentioning
confidence: 99%